Analisis Penerapan Arm’s Length Principle Dalam Transaksi Pinjaman - Natama, Reynold Anggiat Manutur; Irawan, Ferry (COMPETITIVE, 2021)
In 2018, many OECD member countries expected the requirements for implementing the arm’s length principle (ALP) to be easier to apply for financial transactions and the OECD responded by issuing Transfer pricing Guidance on Financial Transactions in 2020. It indicates that the implementation of the arm’s length principle in financial transactions is something that requires more attention. This research aims to analyze and elaborate on how to apply the arm’s length principle in overcoming loan interest transfer pricing cases and analyze the effectiveness of its implementation. The research method used is a qualitative approach with a case study analysis of five tax court decisions regarding tax appeal over transfer pricing of loan interest. The results show that the arm’s length principle has not been implemented effectively in Indonesia. The appellee (Directorate General of Taxation) and the appellant (taxpayer) could not provide a strong argument to determine a proper price based on ALP. However, the Tax Court decided to win taxpayer lawsuit. The significant finding of this research is ALP implementation is challenging to be achieved by both taxpayers and tax authority.